2008
DOI: 10.1177/0269216308095701
|View full text |Cite
|
Sign up to set email alerts
|

Pain assessment tools in palliative care: an urgent need for consensus

Abstract: At present, there is no universally accepted cancer pain assessment tool for use in palliative care (PC). The European Palliative Care Research Collaborative (EPCRC), therefore, aims to develop an international consensus-based computerised pain assessment tool. As part of this process, we have performed (1) a literature review on pain assessment tools for use in the PC and (2) an international expert survey to gain information on the relevant dimensions for pain assessment in PC. 230 publications were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 44 publications
1
60
0
Order By: Relevance
“…They felt patients found it difficult to describe their pain or use numerical rating scales despite guidance suggesting routine use [23]. This may be because such scales are designed primarily as research tools and patients are seldom involved in their development [24,25]. This corresponds with the findings of our recent qualitative study in patients with advanced cancer; patients found the use of numerical rating scales challenging and did not equate 'pain control' with being pain-free, or having a score at a certain level.…”
Section: Discussionmentioning
confidence: 99%
“…They felt patients found it difficult to describe their pain or use numerical rating scales despite guidance suggesting routine use [23]. This may be because such scales are designed primarily as research tools and patients are seldom involved in their development [24,25]. This corresponds with the findings of our recent qualitative study in patients with advanced cancer; patients found the use of numerical rating scales challenging and did not equate 'pain control' with being pain-free, or having a score at a certain level.…”
Section: Discussionmentioning
confidence: 99%
“…26 For example the clinician is requested to enquire about pain intensity at the time of assessment and at its worst over the last twenty fours using a 0 -10 numerical rating scale. 27,28 An adapted version of the symptom assessment checklist described by Homsi et al, 2006 was utilised in that the symptoms were grouped according to the respiratory system, cardiovascular, central nervous systems and the upper, middle and lower gastrointestinal system to aid recall. 16 The…”
Section: Methodsmentioning
confidence: 99%
“…This may be due to several factors, of which lack of systematic assessment has been recognized in several studies. A review of pain assessment tools for self-reporting concluded that intensity, location, and time of occurrence are the most important aspects to include in a comprehensive assessment, as they may give the physician important clues for the pain diagnosis and treatment [10], [11].…”
Section: A Backgroundmentioning
confidence: 99%